2022
DOI: 10.1108/jhti-03-2022-0094
|View full text |Cite
|
Sign up to set email alerts
|

The effect of deepfake video advertisements on the hotel booking intention of tourists

Abstract: PurposeThis study aims to investigate the effect of deepfake video advertisements on hotel booking intention by applying the media richness theory (MRT) and information manipulation theory (IMT).Design/methodology/approachA quantitative survey was conducted using a structured questionnaire to understand the effect of deepfake hotel video advertisements on booking intention. A large cross-section of 1,240 tourists was surveyed and data were analyzed with partial least squares structural equation modeling (PLS-S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 99 publications
(198 reference statements)
0
4
0
Order By: Relevance
“…The study in [26] explored the difference in detection performance between human observers and automated systems by comparing their abilities to identify deepfake videos in the presence of noisy channels. The interesting work in [27] examined tourists' visit intention by watching deepfake destination videos, and found that the factors that affect the tourists' visit intention after watching deepfake videos include information manipulation tactics, trust and media richness, while perceived deception does not influence tourists' visit intention. The study in [28] shows that people are more likely to feel uncertain than to be misled by political deepfakes, but this resulting uncertainty, in turn, reduces trust in news on social media.…”
Section: Related Workmentioning
confidence: 99%
“…The study in [26] explored the difference in detection performance between human observers and automated systems by comparing their abilities to identify deepfake videos in the presence of noisy channels. The interesting work in [27] examined tourists' visit intention by watching deepfake destination videos, and found that the factors that affect the tourists' visit intention after watching deepfake videos include information manipulation tactics, trust and media richness, while perceived deception does not influence tourists' visit intention. The study in [28] shows that people are more likely to feel uncertain than to be misled by political deepfakes, but this resulting uncertainty, in turn, reduces trust in news on social media.…”
Section: Related Workmentioning
confidence: 99%
“…Customers seeking a hotel may feel more inclined to book a hotel after watching deepfake hotel videos. Therefore, there is a need to assess the impact of deepfake video advertisement with more investigation within its relationship with other types of information manipulations tactics that eventually affect the customers intentional behaviors (Sivathanu & Pillai, 2022).…”
Section: Deepfakes and Perceived Media Richnessmentioning
confidence: 99%
“…In the hotel industry, various hotel advertisements are displayed on technology platforms to attract consumers (Kim & Jun, 2016;Leung & Jiang, 2018;Stafford, 2020). Therefore, booking intention refers to the readiness of online customers to reserve accommodation through the digital platforms of service providers (Sivathanu & Pillai, 2022).…”
Section: Hotel Booking Intentionmentioning
confidence: 99%
See 1 more Smart Citation